LaTeX style files for UiTM exam papers and online submission / Siti Aishah Derani - Derani, Siti Aishah (Faculty of Computer and Mathematical Sciences, 2007)
This project paper is about LaTeX Style Files for UiTM Exams Papers and Online Submission which create a website for lecturers. The website allows lecturers to download a set of files for exam papers using LaTeX style which follow UiTM examination standard. The files will be created using LaTeX, a document processor. It also allows lectures to send a file. The paper also consist the methodology used to develop the website, and design specification. This paper also discusses the advantages of using LaTeX over Microsoft Words and the significance of the online system.